Sudden Cardiac Death due to Giant Cell Myocarditis in a 37-Year-Old Female: Case Report. (9th November 2022) - Nobee, A; Yin, J; Hassler, J; Rong, Y
Abstract: Introduction/Objective: Giant cell myocarditis (GCM) is a rare and aggressive inflammatory process that targets the myocardium and is often rapidly fatal. Most cases have been reported in young to middle aged adults with a slight male predominance. The etiology of this disease is largely unknown, however there is an association with multiple autoimmune disorders. Most patients present with rapidly progressive or fulminant heart failure, arrhythmias, heart block or sudden cardiac death. The incidence of GCM ranges from 0.007% to 0.051% and most cases are confirmed on autopsy examination. Here we present a case of GCM in a young female diagnosed on autopsy. Methods/Case Report: A 37-year-old female presented with shortness of breath and chest pain for a 5-day duration. She had no past medical history and was otherwise well before the onset of symptoms. On admission, she was noted to have clinical findings consistent with heart failure and progressed to cardiogenic shock with ventricular arrhythmias within hours. Despite high dose corticosteroids and other supportive therapy, the patient remained in refractory, vasodilatory shock, in cardiac standstill and eventually died. Findings on autopsy included mild ventricular hypertrophy, petechial hemorrhages through out the atria and ventricles, as well as pulmonary edema and congestion. Microscopic examination showed a diffuse infiltrating pattern of inflammation within the heart, that was composed predominantly of lymphocytes, giant cells, scattered neutrophils, and eosinophils. The lymphocytes were CD3, CD4, CD8 positive and CD20 negative, consistent with a T-cell infiltrate. Gram and GMS stains were negative for bacterial and fungal microorganisms. Focal areas of necrosis without granuloma formation are also noted ruling out sarcoidosis. Results (if a Case Study enter NA): NA. Conclusion: This case demonstrates a rapid manifestation of GCM in a previously healthy individual. GCM must be considered in the differential diagnosis when a young patient presents with cardiac symptoms. Early diagnosis and initiation of targeted therapy is critical for GCM patients' survival.